2009
DOI: 10.3133/cir1331
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and Water Resources Management: A Federal Perspective

Abstract: The best available scientific evidence based on observations from long-term monitoring networks indicates that climate change is occurring, although the effects differ regionally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
97
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(108 citation statements)
references
References 37 publications
(41 reference statements)
0
97
0
5
Order By: Relevance
“…For the management and planning at regional or local scale it has been found that continental or global scale studies of climate variables are not very much useful [20,21]. Therefore, the regional and local level climatic variables studies are required for the same.…”
Section: Introductionmentioning
confidence: 99%
“…For the management and planning at regional or local scale it has been found that continental or global scale studies of climate variables are not very much useful [20,21]. Therefore, the regional and local level climatic variables studies are required for the same.…”
Section: Introductionmentioning
confidence: 99%
“…Climate change is projected to have a variety of effects on water resources including supply reliability, flood risk, health, agriculture, energy and aquatic systems. The main climate drivers that affect water are changing temperature and precipitation and rising global sea levels [14]. Specifically, increasing global temperature has the immediate effect of producing higher evaporation rates, thereby drying soils, increasing irrigation requirements of agriculture, and reducing reservoirs of surface water.…”
Section: Climate Changementioning
confidence: 99%
“…Selected issues about climate change that could be used within an AF for watershed management are listed below (Brekke et al 2009). …”
Section: Climate Changementioning
confidence: 99%
“…In 2009, four federal agencies jointly released an interagency report that explores strategies for improving water management by tracking, anticipating, and responding to climate change (Brekke et al 2009). The agencies included the U.S. Geological Survey (USGS), USACE, USBR, and the National Oceanic and Atmospheric Administration (NOAA).…”
Section: Climate Changementioning
confidence: 99%